Bilateral skull fracture with massive epidural hematoma secondary to pin-type head fixation in a pediatric patient: Case report and review of the literature - Parenrengi, M. Arifin (Int J Surg Case Rep, 2019)
INTRODUCTION: A head fixation device containing pins is common equipment used in neurosurgical procedures. Previous reports analysed some of the complications associated with the application of this device for adults and children, even the indications for the use in pediatric are not well defined. CASE PRESENTATION: An 11-year-old girl diagnosed with non-communicating hydrocephalus, caused by posterior fossa tumor. During the surgery, complications were found in the form of acute epidural hematoma due to head fixation pins. So, the operation was stopped. Emergent CT scan was carried out and showed a bilateral skull fracture and a massive right-sided epidural hematoma. An emergency craniotomy for clot removal was performed and five days later, a second surgery was carried out uneventfully for the residual tumor. The patient fully recovered after the second surgery. DISCUSSION: Complications due to the use of a pin head fixation are easier to occur in pediatric patients, because the bones are thinner and need more carefull strategy when pinning. With promp identification of any complications and earlier treatment, the good outcome will be achieved. We compared our case report with published literature in order to suggest the way to prevent this complication. CONCLUSION: Skull fractures and associated epidural hematomas in pediatric patients need to be considered as possible complications of the pin-type head fixation application. The head fixation devices in pediatric need to be used with great caution and knowing the risk factors, safe technique for application and management of complications will prevent worse outcome.